Structure-based design of new potent and highly selective PARP-1 inhibitor for treating colorectal cancer - Chunying Jiang; Shudan Yang; Yuting Wang; Liyuan Du; Miao-Miao Niu; Dongli Zhang (Journal of Enzyme Inhibition and Medicinal Chemistry)
Poly (ADP-ribose) polymerase 1 (PARP-1) exhibits high expression levels in colorectal cancer (CRC) patients and participates in multiple DNA damage repair pathways, thereby emerging as an attractive target. Herein, we identified a series of PARP-1 inhibitors (termed as compounds 1-6) by pharmacophore modelling, virtual screening and biological evaluation. Enzyme inhibition assays demonstrated that compound-5 significantly inhibited PARP-1 activity (IC50 = 0.07 ± 0.01 nM) and exhibited high selectivity for PARP-1 among 63 different kinases. Molecular dynamic simulations indicated that compound-5 stably bound to the catalytic domain of PARP-1. Cellular assays demonstrated that compound-5 significantly inhibited the proliferation of a panel of human CRC cell lines (HCT116, SNU-1, Caco-2, HT-29). The data suggest that compound-5 may be a highly potent and selective PARP-1 inhibitor for CRC therapy.